Effects of shade on guinea grass genotypes Megathyrsus maximus (Poales: Poaceae) - Malaviya, Devendra Ram (2020)
Introduction: Light stress is an important factor limiting the biomass yield while combining forage production with crops or forestry. Guinea grass is a widely adapted perennial fodder grass. The species exhibits high degree of variation for morphology, adaptation and biomass yield. Objective: Since there is a need in identifying shade adapted forage grasses for the expanding area under agroforestry/silvipastures, the present investigation took the task of understanding how the morphologically distinct genotypes of guinea grass respond under different shaded intensities. Methods: In the present study, forty-four genotypes related with the shade response were studied in varying shading conditions (pure sunlight, 25, 50 and 75 % shade) created artificially. Results: Based on green and dry matter yields ranking, the genotype IG 01-98 performed the best followed by genotypes IG 01-92, IG 97-5, IG 97-6 and IG 01-89 in decreasing order. Particularly, IG 01-93 was identified as the best performing under 50 % shading conditions. On the other hand, most of the top ranking genotypes performed well both under open and up to 50 % of shade. Morphologically, these genotypes were taller and possessed longer and broader leaves. Under shaded conditions (over 50 %), leaf length and width showed an increasing trend compared to open conditions. Also, chlorophyll content increased with shading intensity. Conclusions: Most of the genotypes collected from the southern Indian humid tropical environment with early flowering nature were tolerant to shade. Differential genotypic response was observed for biomass yield and yield attributes under shade. The study established appreciable variability for shade tolerance among genotypes